Adverbes de localisation temporelle et enchaînement spatio-temporel : Le cas de dehors et autres expressions apparentées - Chokri Rhibi (Corela)
This article addresses the discursive functions of two spatial localization adverbs dehors et au dehors. The overall aim of this paper is to highlight their role in discourse structuring. The article examines the combinatory characteristics and the usage conditions of these two expressions in narrative sequences. Finally, we intend to show that -in some contexts- the spatial and temporal values of these expressions can be split.